Endothelial-derived microvesicles promote pro-migratory cross-talk with smooth muscle cells by a mechanism requiring tissue factor and PAR2 activation - Featherby, Sophie J.; Ettelaie, Camille (Frontiers in Cardiovascular Medicine, 2024)
Introduction Microvesicles (MV) released by endothelial cells (EC) following injury or inflammation contain tissue factor (TF) and mediate communication with the underlying smooth muscle cells (SMC). Ser253-phosphorylated TF co-localizes with filamin A at the leading edge of migrating SMC. In this study, the influence of endothelial-derived TF-MV, on human coronary artery SMC (HCASMC) migration was examined. Methods and Results MV derived from human coronary artery EC (HCAEC) expressing TFWt accelerated HCASMC migration, but was lower with cytoplasmic domain-deleted TF. Furthermore, incubation with TFAsp253-MV, or expression of TFAsp253 in HCASMC, reduced cell migration. Blocking TF-factor VIIa (TF-fVIIa) procoagulant/protease activity, or inhibiting PAR2 signaling on HCASMC, abolished the accelerated migration. Incubation with fVIIa alone increased HCASMC migration, but was significantly enhanced on supplementation with TF. Neither recombinant TF alone, factor Xa, nor PAR2-activating peptide (SLIGKV) influenced cell migration. In other experiments, HCASMC were transfected with peptides corresponding to the cytoplasmic domain of TF prior to stimulation with TF-fVIIa. Cell migration was suppressed only when the peptides were phosphorylated at position of Ser253. Expression of mutant forms of filamin A in HCASMC indicated that the enhancement of migration by TF but not by PDGF-BB, was dependent on the presence of repeat-24 within filamin A. Incubation of HCASMC with TFWt-MV significantly reduced the levels of Smoothelin-B protein, and upregulated FAK expression. Discussion In conclusion, Ser253-phosphorylated TF and fVIIa released as MV-cargo by EC, act in conjunction with PAR2 on SMC to promote migration and may be crucial for normal arterial homeostasis as well as, during development of vascular disease.